2023
DOI: 10.3390/vaccines11101517
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Knowledge, Attitudes, and Behaviors toward HPV Infection and Vaccination among University Students in Italy

Gabriella Di Giuseppe,
Silvia Angelillo,
Aida Bianco
et al.

Abstract: Background: This survey investigated the knowledge, attitudes, and behaviors towards HPV preventive measures among university students in Italy and their associated factors. Methods: The cross-sectional survey was conducted between November 2022 and April 2023. Results: Only 41.7% knew about HPV infection and the main preventive measures. Multilevel mixed-effects logistic regression analysis showed that females, those aged 25–30 years, those who have had oral sex, those who had received information about HPV i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This study is part of a larger project that was also aimed at investigating the level of knowledge, the attitudes, and the behaviors towards the HPV preventive measures among university students and the associated factors [ 17 ]. Briefly, the participants, recruited with a two-stage cluster method between November 2022 and September 2023, were 18–30 years old students attending courses in medicine and surgery, healthcare professions, pharmacy, biology, and sports science in three public universities in Southern Italy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is part of a larger project that was also aimed at investigating the level of knowledge, the attitudes, and the behaviors towards the HPV preventive measures among university students and the associated factors [ 17 ]. Briefly, the participants, recruited with a two-stage cluster method between November 2022 and September 2023, were 18–30 years old students attending courses in medicine and surgery, healthcare professions, pharmacy, biology, and sports science in three public universities in Southern Italy.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were informed of the objectives of the study, how to return the saliva and urine samples and the written informed consent form to the research team, that the participation was voluntary, that all the information collected would be processed and analyzed anonymously, and that no compensation or gift would be given if they answered the questionnaire or provided the biological samples. Students were asked to fill in a self-administered questionnaire that has already been described [ 17 ] and to self-collect a urine and saliva sample. Briefly, the first section was on socio-demographic and general characteristics; the second section investigated level of knowledge about the HPV; the third section was on concerns about the risk of acquiring an HPV infection and related disease or a sexually transmitted disease (STD), and on attitudes about preventive measures (vaccination, Pap test, DNA HPV test) for HPV infection and related diseases; the fourth section asked about the immunization status regarding HPV and the willingness to receive the HPV vaccine; and the last section was on sources of HPV-infection and related preventive measures information, and the need for additional information.…”
Section: Methodsmentioning
confidence: 99%
“…Among healthcare professionals, studies have identified gaps in knowledge about the Human Papillomavirus (HPV) vaccine, particularly regarding its functioning and potential benefits ( 44 ). A recent study conducted in Italy among university students enrolled in health programs such as medicine, healthcare and pharmacy, showed major gaps in knowledge of HPV infection and preventive measures, and the self-reported vaccination rate was very low ( 45 ). This lack of knowledge influences their willingness to get vaccinated, recommend vaccination to their patients, or participate in HPV vaccination recommendation programs ( 44 ).…”
Section: Introductionmentioning
confidence: 99%